Le débordement du sens : quelques métonymies et métaphores syntaxiques de l’anglais et du français - Paul LARREYA (E-REA)
Grounded on a distinction between the mental component and the linguistic component of metonymy and metaphor, this study, after a brief survey of their essential mental characteristics, proposes the outline of a typology of the two tropes. Le last section of the paper revisits the mental component and examines a set of phenomena which can be collectively called metonymic identification and whose nature is not fundamentally linguistic – they pertain to cognition and affect.